The Impact of Social Responsibility and Organizational Accountability on the Performance of Public Librarians in Iran / Soltani-Nejad, N., Jahanshahi, M., Karim Saberi, M., Ansari, N., & Zarei-Maram, N. (2022). The relationship between social responsibility and public libraries accountability: The mediating role of professional ethics and conscientiousness. Journal of Librarianship and Information Science, 54(2), 306–324. https://doi.org/10.1177/09610006211014260 - Miller-Nesbitt, Andrea (Evidence Based Library and Information Practice, 2023)
Objective – To determine how librarians' perceptions of public libraries' social responsibility and accountability within society affect their professional ethics and conscientiousness.Design – Quantitative, survey questionnaire.Setting – Public libraries in Iran.Subjects – Survey respondents (N=362) were public librarians* (see note below).Methods – The authors created a theoretical model based on six separate hypotheses, describing the relationship between the following variables: corporate social responsibility, organizational accountability, professional ethics, and conscientiousness. A questionnaire was distributed to the participants. SPSS 21.0 was used for the analysis of demographic data and SMART PLS 3.0 was used to assess the theoretical model.Main Results – The results show a significant, positive, and direct relationship between the variables being studied (corporate social responsibility, organizational accountability, professional ethics, and conscientiousness), therefore confirming the relevance of the authors’ theoretical model.Conclusion – The results of this study demonstrate the importance of promoting the social responsibility and organizational accountability efforts of public libraries. The data suggest that doing so will strengthen the positive perception of the library amongst employees, which will in turn have a positive effect on their professional ethics and conscientiousness. The authors suggest that library managers need to create a culture of accountability and ethics within libraries. They can do so by incorporating ethics and social responsibility in decision-making and policies. Additionally, the authors propose that professional ethics training in library curricula and continuing education would provide librarians with the knowledge necessary when encountering ethical dilemmas on the job.